Culling Dogs for Zoonotic Visceral Leishmaniasis Control: The Wind of Change. Issue 2 (February 2019) - Dantas-Torres, Filipe; Miró, Guadalupe; Bowman, Dwight D.; Gradoni, Luigi; Otranto, Domenico
Abstract : Visceral leishmaniasis, caused by Leishmania infantum, is a zoonosis, and culling seropositive dogs has been recommended to control the disease in some endemic countries. However, no scientific evidence supports the effectiveness of this strategy to reduce the incidence of visceral leishmaniasis. Economic and ethical issues concerning dog culling are discussed.